2008
DOI: 10.1002/icd.581
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relations between effortful and attentional control and symptoms of psychopathology in middle childhood

Abstract: Elucidating the genetic and environmental etiology of effortful control (mother and father report at two time points), attentional control (observer reports) and their associations with internalizing and externalizing symptoms (mother and father report) is the central focus of this paper. With a sample of twins in middle childhood participating in the Wisconsin Twin Project, broad sense heritability for parental report effortful control ranged from 68–79%, with a slightly higher heritability estimate of 83% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 78 publications
(79 reference statements)
9
96
1
1
Order By: Relevance
“…Few studies have yet considered EC in relation to depressive symptoms, but those doing so have generally found low levels of EC to be associated with elevated depressive and internalizing symptoms (see Carver et al, 2008). This is true both concurrently (e.g., Loukas & Roalson, 2006;Muris, 2006;Verstraeten, Vasey, Raes, & Bijttebier, 2009;Yap et al, 2011) and prospectively (Lemery-Chalfant, Doelger, & Goldsmith, 2008;Oldehinkel, Hartman, Ferdinand, Verhulst, & Ormel, 2007), though studies looking specifically at depressive symptoms have thus far not found a prospective association (Loukas & Roalson, 2006;Verstraeten et al, 2009). Similarly, research on conscientiousness demonstrates a clear negative association with concurrent depressive symptoms, though studies examining the role of conscientiousness in the development of depressive symptoms over time are lacking (see Klein et al, 2011;Kotov, Gamez, Schmidt, & Watson, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Few studies have yet considered EC in relation to depressive symptoms, but those doing so have generally found low levels of EC to be associated with elevated depressive and internalizing symptoms (see Carver et al, 2008). This is true both concurrently (e.g., Loukas & Roalson, 2006;Muris, 2006;Verstraeten, Vasey, Raes, & Bijttebier, 2009;Yap et al, 2011) and prospectively (Lemery-Chalfant, Doelger, & Goldsmith, 2008;Oldehinkel, Hartman, Ferdinand, Verhulst, & Ormel, 2007), though studies looking specifically at depressive symptoms have thus far not found a prospective association (Loukas & Roalson, 2006;Verstraeten et al, 2009). Similarly, research on conscientiousness demonstrates a clear negative association with concurrent depressive symptoms, though studies examining the role of conscientiousness in the development of depressive symptoms over time are lacking (see Klein et al, 2011;Kotov, Gamez, Schmidt, & Watson, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…As such, two models in the literature suggest that some form of effortful cognitive control is an important developmental skill in inhibiting attentional biases to threat. There is evidence supporting this idea: (1) anxious children show deficits in effortful attentional control and have difficulty in disengaging from unpleasant stimuli (Derryberry and Reed 2002;Lonigan et al 2004); (2) low effortful control (over attention) is related to changes in anxiety-related maladjustment in children with an average age of 7 (Eisenberg et al 2009); (3) attentional control is negatively related to anxiety symptoms in 8-to 13-year-old children (Muris et al 2004); (4) the relationship between negative affectivity (a predictor of anxiety symptoms) and selective attention to threat in high trait anxious adolescents is moderated by effortful control (Lonigan and Vasey 2009); and (5) anxiety and effortful control might also share common genes (Lemery-Chalfant et al 2008) suggesting that the two constructs are genetically linked. Therefore, the failure to develop effortful and attentional control in middle to late childhood (e.g., 10-14 years) represents a viable developmental mechanism by which common attentional biases to threat may become extreme and maladaptive.…”
Section: Child Development and Attentional Biasesmentioning
confidence: 98%
“…It is measured via indices of abilities to regulate attention, to persist, to delay, and to inhibit (or activate) behavior (Kochanska, Murray, & Harlan, 2000;Rothbart & Bates, 2006). Although effortful control is moderately heritable, parents who are positive and supportive can promote children's effortful control (e.g., Stormshak, Fosco, & Dishion, 2010); in fact, effortful control is significantly influenced by the environment (Lemery-Chalfant, Doelger, & Goldsmith, 2008). Some indices of effortful control (e.g., inhibitory control) are related to executive functioning, cognitive skills especially important for achievement (Carlson, 2005;Carlson & Wang, 2007); however, important distinctions have differentiated the two constructs (Blair & Razza, 2007;Zhou, Chen, & Main, 2011), including that effortful control is specifically a facet of temperament.…”
Section: The Mediating Factor Of Effortful Controlmentioning
confidence: 99%